1993
DOI: 10.1248/bpb.16.970
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Taurine on the Biomembrane against Damage Produced by Oxygen Radicals.

Abstract: The effect of taurine in protecting biomembrane against oxygen radicals was investigated using canine erythrocytes. 2,2'-Azobis(2-amidinopropane) dihydrochloride (AAPH), a water-soluble azo-compound, was used as the oxygen-radical generator. Taurine suppressed erythrocyte hemolysis more effectively than alpha-alanine, used for comparison. To clarify the relationship to the lipid peroxidation, the amount of lipid peroxide was measured using liposomes prepared with egg yolk lecithin. However, the peroxidation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 1 publication
2
37
0
Order By: Relevance
“…33) Therefore, it has been suggested that these eŠects of taurine may be related to its inhibitor eŠect on lipid peroxidation and W or its stabilizator eŠect on membranes. [23][24][25]33) However, when normal rabbit erythrocytes were incubated with H2O2 in the presence of taurine, no changes were observed in the osmotic fragility test of erythrocytes (Fig. 1B) and MDA levels (Fig.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…33) Therefore, it has been suggested that these eŠects of taurine may be related to its inhibitor eŠect on lipid peroxidation and W or its stabilizator eŠect on membranes. [23][24][25]33) However, when normal rabbit erythrocytes were incubated with H2O2 in the presence of taurine, no changes were observed in the osmotic fragility test of erythrocytes (Fig. 1B) and MDA levels (Fig.…”
mentioning
confidence: 94%
“…22) In addition, some investigators have reported that taurine has an ability to suppress erythrocyte hemolysis caused by oxidative damage in in vitro conditions. [23][24][25] However, there is no adequate report about the eŠects of taurine on erythrocyte hemolysis in in vivo conditions. Therefore, theˆrst aim of this study was to estimate the contribution of oxidative stress to hypercholesterolemia-induced hemolytic anemia in rabbits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Taurine (2-amino ethanesulfonic acid) an end-product of sulfur amino acid metabolism, is one of the most abundant free amino acids in the body. The membrane stabilizing, free radical scavenging, and osmoregulatory roles of taurine have been well documented [49,50] . In one study, taurine enhanced viability and reduced lipid peroxidation in cryopreserved islets.…”
Section: Rat → Ratmentioning
confidence: 99%
“…Therefore, antioxidant therapy has become an attractive strategy. 3,4) Red blood cell membrane is consisted of abundant polyunsaturated fatty acids that are very susceptible to free radical mediated peroxidation.…”
Section: Introductionmentioning
confidence: 99%